Which Frailty Evaluation Method Can Better Improve the Predictive Ability of the SASA for Postoperative Complications of Patients Undergoing Elective Abdominal Surgery? - Yin Y; Jiang L; Xue L (Dove Medical Press, 2022)
Yanyan Yin,1 Li Jiang,2 Lixin Xue3 1Department of Neurological Rehabilitation, Beijing Rehabilitation Hospital, Capital Medical University, Beijing, 100144, People's Republic of China; 2Department of Critical Care Medicine, Xuanwu Hospital, Capital Medical University, Beijing, 100053, People's Republic of China; 3Department of General Surgery, Fuxing Hospital, Capital Medical University, Beijing, 100038, People's Republic of ChinaCorrespondence: Li Jiang, Department of Critical Care Medicine, Xuanwu Hospital, Capital Medical University, No. 45 Changchun Street, Xicheng District, Beijing, 100053, People's Republic of China, Tel +8613601366055, Email jianglipaper@sina.comPurpose: To determine which frailty method can better improve the predictive ability of the Surgical Apgar Score combined with American Society of Anesthesiologists physical status classification (SASA).Patients and Methods: A prospective cohort study was conducted. A total of 194 elderly patients undergoing elective abdominal surgery were included. Preoperative frailty using FRAIL questionnaire, frailty index (FI), Clinical Frailty Scale (CFS) and SASA scores was assessed. Primary outcome was in-hospital Clavien-Dindo ≥grade II complications. Multiple logistic regression was used to examine the association between frailty and complications. Receiver operating characteristic curves were used to explore the predictive ability of frailty.Results: According to the FRAIL, FI and CFS criteria, the prevalence of frailty in the study population was 43.8%, 32.5%, and 36.6%, respectively. After adjusting for all covariates, frailty was significantly associated with postoperative complications in hospital by FRAIL [odds ratio: 5.11, 95% CI: 1.41- 18.44, P = 0.013], by FI [OR: 4.25, 95% CI: 1.21- 14.90, P = 0.024] and by CFS [OR: 5.10, 95% CI: 1.52- 17.17, P = 0.008]. The area under the curve (AUC) for SASA was 0.768 (95% CI: 0.702- 0.826). Addition of frailty assessment (FRAIL, FI and CFS) increased the AUC to 0.787 (95% CI: 0.722- 0.842), 0.798 (95% CI: 0.734- 0.852), and 0.815 (95% CI: 0.753- 0.867), respectively. Compared to SASA, only addition of CFS had a significant difference (P = 0.0478).Conclusion: Frailty is an effective predictor of postoperative complications in elderly Chinese patients undergoing elective abdominal surgery. Frailty assessment of CFS can better improve the predictive ability of SASA.Keywords: frailty assessment, risk assessment tool, postoperative complication